Doubly Cavitand‐Capped Porphyrin Capsule by Hydrogen Bonds. Issue 8 (20th January 2016) - Kishimoto, Kazuki; Nakamura, Munechika; Kobayashi, Kenji
Abstract: The components of a 1:2 mixture of meso ‐tetrakis(4‐dodecyl‐3, 5‐dihydroxyphenyl)porphyrin (1 ) and a bowl‐shaped tetrakis(4‐pyridylethynyl)cavitand (2 ) in CDCl3 or C6 D6 self‐assemble quantitatively into the doubly cavitand‐capped porphyrin capsule2⋅1⋅2 through eight ArOH⋅⋅⋅ Npy hydrogen bonds. Capsule2⋅1⋅2 possesses two cavities divided by the porphyrin ring and encapsulates two molecules of 1‐acetoxy‐3, 5‐dimethoxybenzene (G ) as a guest to formG /G @(2⋅1⋅2 ). Remarkable solvent effect was observed, in which the apparent association constant of2⋅1⋅2 withG in C6 D6 was much greater than that in CDCl3 . Abstract : Porphyrin sandwich ! A 1:2 mixture of resorcinol‐porphyrin1 and pyridylethynyl cavitand2 self‐assembles into doubly cavitand‐capped porphyrin capsule2⋅1⋅2 through eight ArOH⋅⋅⋅ Npy hydrogen bonds, which encapsulates two guest molecules (see figure).